Fasciola hepatica infection modifies IgG1 specific immune response to foot-and-mouth disease virus induced by vaccination - Costa, Monique; Mansilla, Florencia Celeste; Sala, Juan Manuel; Saravia, Anderson; Ubios, Diego; Lores, Pablo; Capozzo, Alejandra; Freire, Teresa (Elsevier, 2024)
Fasciola hepatica, a worldwide distributed helminth, has a robust immunoregulatory effect in the host, increasing the susceptibility to secondary infections. Foot and mouth disease (FMD) is a highly contagious acute vesicular viral disease effectively controlled by vaccination in endemic regions. Despite the evidence of immunoregulatory effects, the impact of fasciolosis on the immune response induced by FMD vaccination in cattle has never been assessed. Our objective was to evaluate whether the infection by F. hepatica in cattle influences the long-term immunity elicited by the currently used commercial FMD-inactivated vaccines. Aberdeen Angus steers negative for F. hepatica were vaccinated twice against FMD virus (FMDV) during the first 6 months of age using a commercial oil vaccine formulated with A24/Cruzeiro and O1/Campos strains. When maternal antibodies against F. hepatica were weaned (18––20 months of age) animals were divided into groups of 12 and infected or mock-infected with 500 metacercariae/animal. Individual serum samples were collected at 0-, 28-, 59-, 87- and 157-days post-infection (dpi). Indirect ELISAs were used to detect A24/Cruzeiro specific bovine IgG and IgG subtypes. The total IgG antibody levels and avidity against FMDV did not show significant differences between all the groups. The commercial vaccine induced higher IgG2 than IgG1 titers in vaccinated animals. Anti-FMDV IgG1 levels significantly decreased in the infected group at 28 dpi. In addition, the avidity of IgG1 FMDV-specific antibodies at day 28 in the infected group was reduced compared to the control. These results show that F. hepatica infection modified anamnestic responses against FMDV, reducing serum IgG1 titers and avidity. To our knowledge, this is the first report of immune-regulation of F. hepatica altering the immune response of FMD vaccines, one of the most globally used animal vaccines.